Parasitic Mite Fauna in Asian Poultry Farming Systems - Sparagano, Olivier A. E.; Ho, Jeffery (Frontiers in Veterinary Science, 2020)
The ubiquitous presence of hematophagous avian mites threatens the poultry industry in Asia and worldwide, adversely affecting the quality and quantity of eggs and chicken meat produced by affected flocks; leading to considerable economic loss and welfare-related issues. The role of these blood-feeding arthropods as disease vectors is increasingly recognized as they may carry Salmonella spp or avian influenza for instance and many more and induce contact dermatitis in birds, pets and humans. The poultry mites, Dermanyssus gallinae (De Geer, 1778) (Mesostigmata: Dermanyssidae, known as the Poultry Red Mite (PRM)), Ornithonysus sylviarum (Canestrini and Fanzago, 1877, known as the Northern Fowl Mite (NFM)), and Ornithonyssus bursa (Berlese 1888) (Mesostigmata: Macronyssinae, known as the Tropical Fowl Mite TFM)) are endemic species across the Asian continent; the burrowing mite, Knemidocoptes mutans (Sarcoptiforms: Knemidocoptidae), and the cystic mite, Laminosioptes cysticola (Acariformes: Laminosioplidae) are less frequently reported. Notably, multiple mite species co-infested the same flocks with other ectoparasites such as lice, fleas, and ticks. Considering global climate change, the high number of poultry backyard systems more difficult to treat, the incidence of avian mite infestation is expected to increase as Asian production expands. The tropical fowl mite, Ornithonyssus bursa, may start to colonize sub-tropical nations where the seasonal temperature is comparable to tropical regions. Pyrethroids, organophosphates, carbamates, and macrocyclic lactones are licensed acaricides for use in China, Japan, and India. In recent years, the development of acaricide resistance has compromised the efficacy of chemical control measures. Several bio-acaricides based on plant and fungal extracts are being investigated. Judicious integration of multiple approaches to manage poultry mite infestation is advised. In this article, we review the prevalence, geographical distribution, zoonotic potential and control measures of avian mites in poultry farms with a focus on Dermanyssus spp. and Ornithonyssus spp in Asia.